Cross-Linking Effects Dictate the Preference of Galectins to Bind LacNAc-Decorated HPMA Copolymers - Bertuzzi, Sara (Int J Mol Sci, 2021)
The interaction of multi-LacNAc (Galβ1-4GlcNAc)-containing N-(2-hydroxypropyl) methacrylamide (HPMA) copolymers with human galectin-1 (Gal-1) and the carbohydrate recognition domain (CRD) of human galectin-3 (Gal-3) was analyzed using NMR methods in addition to cryo-electron-microscopy and dynamic light scattering (DLS) experiments. The interaction with individual LacNAc-containing components of the polymer was studied for comparison purposes. For Gal-3 CRD, the NMR data suggest a canonical interaction of the individual small-molecule bi- and trivalent ligands with the lectin binding site and better affinity for the trivalent arrangement due to statistical effects. For the glycopolymers, the interaction was stronger, although no evidence for forming a large supramolecule was obtained. In contrast, for Gal-1, the results indicate the formation of large cross-linked supramolecules in the presence of multivalent LacNAc entities for both the individual building blocks and the polymers. Interestingly, the bivalent and trivalent presentation of LacNAc in the polymer did not produce such an increase, indicating that the multivalency provided by the polymer is sufficient for triggering an efficient binding between the glycopolymer and Gal-1. This hypothesis was further demonstrated by electron microscopy and DLS methods.